Parallel multi-structure decellularisation of a porcine three-dimensional right ventricular outflow tract valved xenograft for use in paediatric congenital cardiac surgery. (10th June 2022) - Harris, A; Iacobazzi, D; Carrabba, M; Caputo, M; Suleiman, S
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation Background: Tetralogy of Fallot is the most common cyanotic congenital heart disease and requires right ventricular outflow tract (RVOT) replacement. RVOT substitutes are suboptimal, functionally deteriorating within a few years and necessitating a series of surgical reinterventions. An optimal prosthetic that mimics the structural and mechanical properties of native tissue is desirable. However, due to inadequate homo/autograft availability for neonates and infants, xenografts are commonly used in paediatric cardiac surgery. Current xenografts are limited by lack of growth, susceptibility to calcification, and limited remodelling capacity. Decellularisation to remove immunogenic antigens on the animal-derived tissue reduces the risk of graft rejection. Decellularisation conditions are critical: harsh treatment will disrupt extracellular matrix components vital for in vivo recellularisation; conversely, a too mild treatment may lead to incomplete cell removal and graft degeneration. Decellularisation of valved conduits poses a unique challenge as the valve structure differs significantly to that of the artery. The latter is thicker and stronger, requiring harsher detergents which could damage the valve. Purpose: This research optimises an in vitro decellularisation protocol for simultaneous removal of porcine cells from the right ventricle (RV), pulmonary artery (PA), and pulmonary valve (PV). We ultimately plan to recellularise the cell-free RVOT scaffold with autologous mesenchymal stem cells via a tissue-engineering approach, endowing the xenograft with growth capacity and improved biocompatibility compared to existing products, thus overcoming the limitations of the currently used replacement grafts. Methods: The integrated valved RVOT conduits were harvested from pigs and mounted in a temperature-controlled bioreactor chamber. Decellularisation solutions were circulated through the lumen and around the outside of the submerged conduit under constant flow, with extended sodium dodecyl sulfate and nuclease washes. Histological assessment of the RV, PA, and PV by Heamatoxylin and Eosin, for nuclei detection, and Elastin van Gieson's staining, for elastin and collagen content, report on decellularisation success. Results: Preliminary results demonstrate effective decellularisation of the RV, PA, and PV in both the valved conduit decellularised immediately after harvesting and following one freeze-thaw cycle. The ability to freeze RVOTs until needed would facilitate production of an accessible surgical product. Images reveal nuclei elimination in each tissue architecture whilst the extracellular matrix composition appears unchanged. Conclusions: Concurrent multi-tissue decellularisation revealed promising structural results, however mechanical properties of the cell-free RVOT must be assessed to deem decellularisation successful. Further experiments are underway to evaluate the scaffold's capacity to support mesenchymal stem cell repopulation.